Safety evaluation of the food enzyme oryzin from the non‐genetically modified Aspergillus ochraceus strain AE‐P - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal, 2024)
Abstract The food enzyme oryzin (EC 3.4.21.63) is produced with the non‐genetically modified Aspergillus ochraceus strain AE‐P by Amano Enzyme Inc. The food enzyme was considered free from viable cells of the production organism. It is intended to be used in nine food manufacturing processes. The dietary exposure to the food enzyme–total organic solids (TOS) was estimated to be up to 0.1 mg TOS/kg body weight (bw) per day in European populations. Genotoxicity tests did not raise a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 1862 mg TOS/kg bw per day, the highest dose tested, which, when compared with the estimated dietary exposure, resulted in a margin of exposure of at least 18,620. A search for the similarity of the amino acid sequence of the food enzyme to known allergens was made and 31 matches were found, including one food allergen (melon). The Panel considered that the risk of allergic reactions upon dietary exposure to this food enzyme, particularly in individuals sensitised to melon, cannot be excluded, but would not exceed the risk from consumption of this food. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.